2014
DOI: 10.1158/1055-9965.epi-13-1285
|View full text |Cite
|
Sign up to set email alerts
|

Body Size, Physical Activity, Early-Life Energy Restriction, and Associations with Methylated Insulin-like Growth Factor–Binding Protein Genes in Colorectal Cancer

Abstract: Background: We investigated body size, physical activity, and early-life energy restriction in relation to colorectal tumors with and without methylated insulin-like growth factor-binding protein (IGFBP) genes, which are putative tumor-suppressor genes.Methods: We determined IGFBP2, IGFBP3, and IGFBP7 promoter CpG island hypermethylation in tumors of 733 colorectal cancer cases from the Netherlands Cohort Study (N ¼ 120,852). Participants self-reported lifestyle and dietary factors at baseline in 1986. Using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…The researchers concluded that in those mostly exposed to hunger during the winter of 1944–1945 in the Netherlands compared with those least exposed, hyper‐methylation in IGFBP genes was associated with a significantly lower risk for colorectal cancer (HR = 0.72, 95%CI 0.52–0.99) (adjusting for BMI at age 20, adult BMI, change in BMI, size of clothes, height, and physical activity). In other words, those mostly exposed who also showed evidence of epigenetic changes that may have been caused by the exposure, were at a lower risk for colorectal cancer . These findings were in accordance with results of two age‐period‐cohort modeling studies, one from Norway, the other from other Nordic countries and Estonia .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The researchers concluded that in those mostly exposed to hunger during the winter of 1944–1945 in the Netherlands compared with those least exposed, hyper‐methylation in IGFBP genes was associated with a significantly lower risk for colorectal cancer (HR = 0.72, 95%CI 0.52–0.99) (adjusting for BMI at age 20, adult BMI, change in BMI, size of clothes, height, and physical activity). In other words, those mostly exposed who also showed evidence of epigenetic changes that may have been caused by the exposure, were at a lower risk for colorectal cancer . These findings were in accordance with results of two age‐period‐cohort modeling studies, one from Norway, the other from other Nordic countries and Estonia .…”
Section: Discussionsupporting
confidence: 87%
“…Recently gene hyper‐methylation analyses are used to trace epigenetic changes that may mediate associations between early‐life exposure to energy restriction and colorectal cancer . A newly published analysis based on “The Netherlands Cohort Study” reported on colorectal cancer risk by hyper‐methylation of certain genes and by exposure to the Dutch hunger, adjusted for body size. The researchers concluded that in those mostly exposed to hunger during the winter of 1944–1945 in the Netherlands compared with those least exposed, hyper‐methylation in IGFBP genes was associated with a significantly lower risk for colorectal cancer (HR = 0.72, 95%CI 0.52–0.99) (adjusting for BMI at age 20, adult BMI, change in BMI, size of clothes, height, and physical activity).…”
Section: Discussionmentioning
confidence: 99%
“…[19, 21, 22] Few studies have examined whether the association between obesity/obesity factors and CRC risk is affected by IGF-I/IR genetic variants. [17, 21, 23]; though the genetic variants have minimal or modest effect on the obesity–CRC relationship, it suggests that genetic variants related to IGF-I/IR traits and their signaling pathways interact with obesity and jointly influence CRC susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…The same researchers also reported significantly increased plasma levels of insulin-like growth factor 1 (IGF-1) binding globulins in the exposed group, a finding that contradicted the expected shortterm response to starvation and that may explain the increased risk for breast cancer over time [23]. Interestingly, a more recent study that examined the relationship between body size, physical activity, early-life exposure to the 'hunger winter,' and associations with methylated IGF-1 binding protein (IGFBPs) genes in colorectal cancer, reported significantly inverse HRs in exposed (vs. non-exposed) subjects in the subgroups of 2 and 3 methylated IGFBP genes, implying that nutritional deprivation in early life may modify cancer risk in adulthood [24].…”
Section: Studies In Non-jewish Populationsmentioning
confidence: 99%